Effects of temperature and pressure on the mechanical and thermodynamic properties of high-boride WB4 from first-principles predictions. (March 2022) - Yang, Ancang; Duan, Yonghua; Peng, Mingjun
Abstract: Tungsten borides with high boron content are widely used in high temperature and high pressure conditions. In this work, the first-principles calculations were employed to investigate the influence of pressure and temperature on the structure, mechanical properties and thermodynamic properties of hp 10-WB4. The results show that hp 10-WB4 is dynamically and thermodynamically stable over a range of temperatures (0–800 K) and pressures (0–35 GPa). In general, the elastic constants and modulus are improved at the appropriate pressure state. The single crystal tensile simulations in the ground state show that hp 10-WB4 has good strength. And the lattice parameters, crystal structure stability, electronic properties, heat capacity, thermal expansion coefficient α, Debye temperature θ D and Grüneisen parameter γ are also investigated at 0–35 GPa pressure and 0–800 K temperature. The thermal expansion coefficient is sensitive to temperature and pressure. The Debye temperature and Grüneisen parameters show the opposite trend, and the effect of temperature and pressure on them is slight. Graphical Abstract: ga1 Highlights: Elastic moduli B, E, and  G of hp10-WB4 increase with the pressure, Maximum stresses and strains in three directions are 80.6 GPa, 49.7 GPa, 26.1 GPa and 20.8%, 14.6% and 12.4%, respectively. The calculated phonon dispersion curve shows that hp10-WB4 is thermodynamically stable.